Innovative Teaching Methods for Delivering Islamic Financial Literacy to Middle School Students - Tazkiyyah, Naila M; Hafidhuddin, Didin; Ibdalsyah, Ibdalsyah; Tanjung, Hendri (PT FORMOSA CENDEKIA GLOBAL, 2024)
The poor financial management among Indonesian society confirms the suboptimal financial literacy rate in the country. With the majority of Indonesians being Muslims, and considering that Islam involves numerous acts of worship requiring financial assets as their object, Islamic financial literacy education is crucial. A solid educational foundation begins with this understanding, motivating this research to explore teaching methods for Islamic financial literacy for elementary school-aged children. Based on qualitative research using library studies and descriptive analysis, it is found that interactive teaching methods can effectively and enjoyably deliver Islamic financial literacy materials to middle school students.